Synthesis of monocrystalline Ca3SiO5 using the optical floating zone method. (July 2016) - Naber, C.; Goetz-Neunhoeffer, F.; Göbbels, M.; Rößler, C.; Neubauer, J.
Abstract: Alite (Ca3 SiO5 /C3 S with low concentrations of foreign ions) is the main constituent of Ordinary Portland Cement. Normally it forms during sintering but with quite low crystal sizes (ca. 30 μm). For experiments on alite hydration behavior monocrystalline grains are required. Due to its incongruent melting behavior and its thermodynamic instability below 1250 °C it is very challenging to obtain large alite single crystals. In the present study, the floating zone method was used for annealing polycrystalline rods of monoclinic and triclinic C3 S just below the melting point of the phase. Large monocrystalline grains (> 500 μm) of the monoclinic (Al, Mg-doped) and triclinic polymorphs could successfully be obtained. Monocrystallinity was demonstrated by electron backscatter diffraction (EBSD). The chemical composition regarding incorporation of foreign ions and thus the resulting crystallographic modification of the C3 S can easily be adjusted. Chemical homogeneity of the synthesized monocrystalline grains was proven by electron probe microanalysis (EPMA).